Predicting work-related behaviour from personality traits and situational characteristics - Wertheimer, Demi (Organisational Psychology, 2022)
The dual influence of person characteristics and situational contexts on behaviour has long been debated on by personality and social psychologists alike. Traditionally, personality traits have been emphasised, whilst the assessment of situational influences has received limited attention. As a result, there has been little progress in understanding how situational contexts impact individuals' daily organisational behaviour – a key imperative of organisational psychology. This study leverages recent developments in situation assessment to investigate the extent to which personality traits and situational characteristics independently, and in combination, predict workrelevant behaviour. Survey response data from 256 South African participants within the International Situations Project (ISP; Baranski et al., 2017) were analysed. Sets of multiple regression analyses were conducted with each of seven work-related behaviours as criteria, using the Big Five personality traits and DIAMONDS situational characteristics as predictors. Next, barebones meta-analysis (Hunter & Schmidt, 1990) of the resulting multiple correlation coefficients was conducted to estimate the relative predictive power of traits vs. situations, averaged across target behaviours. The results revealed that the combination of personality traits and situational characteristics explained more variance in work-related behaviour than their independent effects. Although situational characteristics independently predicted all work-related behaviours, personality traits were not strong predictors of particular behaviours. These findings highlight the importance of integrating knowledge of both traits and situations to enhance our understanding of why people behave the way they do. Practically, results further suggest that organisations may increase the ability to predict employee behaviour on the job by incorporating measures of situations, in combination with traits, into human resource management applications (e.g., personnel selection and assessment).